COMPARISON OF ARTERIAL STIFFNESS INDEX AND TPE/QT RATIO IN NORMOTENSIVE, PREHYPERTENSIVE AND HYPERTENSIVE SUBJECTS - Mehmood, Muhammad Sajid; Hussain, Muhammad Mazhar; Mubarak, Sadia (Pakistan Journal of Physiology, 2018)
Background: When the blood pressure rises, there is decrease in coronary blood flow to the endocardium and mid-myocardial cells, thereby slowing repolarization in these areas. The major underlying pathophysiology in essential hypertension is arterial stiffness. In this study we compared arterial stiffness index (ASI), T wave peak to end interval (Tpe) and Q to T wave (QT) interval on ECG tracings. Methods: It was a cross-sectional study. Written informed consent was obtained from all subjects. Using non-probability convenience sampling a total of ninety (90) male subjects aged 35–55 years were selected and divided into 3 equal groups, i.e., normotensive, prehypertensive and hypertensive. Blood pressure was measured with mercury sphygmomanometer according to the standard protocols. The ASI was calculated from digital volume pulse recorded by photoplethysmography via iWorx-214; physiological interface system. The 12-lead surface EGG was recorded with Delta-1 Plus digital ECG machine. The ECG tracings were scanned and saved in the computer. QTc, cQTp and cTpe/QTc ratio was calculated in normotensive, prehypertensive and hypertensive middle-aged men. These intervals were corrected by Bazzet’s formulae. Results: The ASI was significantly different (p<0.0001) amongst the groups along with QTc and cQTp. However, cTpe intervals and cTpe/QTc were comparable amongst the groups. Conclusion: ASI is major culprit in pathophysiology of hypertension. QTc and cQTp interval are more robust parameter than other ECG markers in detecting trans-mural dispersion of repolarization in prehypertensive and hypertensive subjects. Pak J Physiol 2018;14(2):34–7